Study of The Distribution of Amorphophallus beccarii Engl in The Hiking Trail of Mount Singgalang Nature Park - Hayati, Rifda; Vauzia, Vauzia (Jurnal Biologi Tropis, 2024)
Amorphophallus beccarii is one of the endemic plant of Sumatra, which has the characteristic of compound flowers, and emits a pungent odour that can attract insects such as flies and beetles to pollinate. Amorphophallu beccarii is found growing around the hiking trail of Mount Singgalang Nature Tourism Park, in connection with Mount Singgalang has been used as a Nature Tourism Park, it is feared that it will cause disruption of Amorphophallus beccarii habitat, in addition to the many human activities that carry out climbing activities, its interesting morphological shape is also the reason for the reduced population of Amorphophallus beccarii because it is collected as an ornamental plant. In conservation efforts, research has been carried out on Amorphophallus beccarii Engl Distribution Study in the Mount Singgalang Nature Tourism Park Hiking Trail. This research was conducted in February-March 2024. The research method used was stratified random sampling where sampling was carried out at an altitude of 1000-2000 mdpl along the hiking trail. Data were processed using the morisita index. The results showed that the distribution pattern of Amorphophallus beccarii on the Mount Singgalang hiking trail was clustered.